Food Advertising - Gunter, Barrie. author. aut Link
VII, 303 p.
Keywords: This book provides an up-to-date and comprehensive review and critique of the scientific evidence concerning the prevalence, nature and potential effects of food advertising and other forms of marketing on children. There is growing international concern about the prevalence of childhood obesity and associated health problems. Poor quality diet and nutrition has been blamed. The food and soft drinks industries have been targeted in this context for their promotions of foods and drinks that are high in salt, sugar and fat content. Many of the most widely promoted and consumed food brands fail to meet recommended nutritional standards. What is the evidence for the effects of food promotions on children’s food preferences, diets and health? This book draws on evidence from around the world, reviewing the major studies before presenting a fresh assessment of the state of play. It considers also the issue of food regulation and advertising codes of practices, the need for better and relevant consumer education and socialisation about advertising and nutrition.